Paradigma Liberal dalam Pendidikan Global - Siswanto Masruri (Universitas Islam Indonesia, 2006)
There are at least three paradigms of education in the era of globalization: conservative, liberal, and critic. The paradigms mentioned could be attained through some processes implemented by the performers of global education. The liberal paradigm is of course brought about with the process of liberalization. Liberalism is therefore a paradigm and liberalization is a process. If the liberalization means as the application and cultivation of some strategic initiatives in the educational field, the writer believes that the majority of educational experts will agree with the purpose of the liberal paradigm. But, if it is intended as a free trade, and the cultural commodity of education is the same as the economic one, some of them will refuse it. In the field of education there are still some centralistic and ceremonial practices, so that there wouldn't be any creativity. Consequently, the quality of Indonesian education is far from any other countries like Malaysia. In order to catch up the backwardness in education, the experts are expected to bring about the process of autonomy, decentralization, to consider culture of excellence and social welfare as the most important by developing 4 intelligences. Finally, the social prosperity could be obtained under the frame of global education.